2011
DOI: 10.1182/blood.v118.21.5001.5001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Renal Function on the Pharmacokinetics of Panobinostat in Patients with Advanced Cancer: A Phase I Study

Abstract: 5001 Panobinostat is a potent class I/II/IV oral pan-deacetylase inhibitor which has shown promising clinical activity in patients with multiple myeloma and myelofibrosis, some with compromised renal and hepatic functions. The metabolism mediated by cytochrome P450 3A4 (CYP3A4) and non-CYP pathways is the major clearance pathway of panobinostat, with drug and metabolites being excreted in nearly similar amounts by liver/bile (54.3) and kidneys (40.6). However, the effects of impaired renal and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The effect of renal dysfunction on the pharmacokinetics of panobinostat is also being evaluated in a Phase I study, and preliminary results have been reported. 18 Panobinostat was administered at a dose of 30 mg orally three times weekly with varying degrees of renal dysfunction (mild, moderate or severe according to 24-hour creatinine clearance). Plasma and urine concentrations of panobinostat assessed by liquid chromatography tandem mass spectrometry following administration did not suggest higher drug exposures (C max , AUC, half-life) with increasing severity of renal dysfunction.…”
Section: Panobinostat Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of renal dysfunction on the pharmacokinetics of panobinostat is also being evaluated in a Phase I study, and preliminary results have been reported. 18 Panobinostat was administered at a dose of 30 mg orally three times weekly with varying degrees of renal dysfunction (mild, moderate or severe according to 24-hour creatinine clearance). Plasma and urine concentrations of panobinostat assessed by liquid chromatography tandem mass spectrometry following administration did not suggest higher drug exposures (C max , AUC, half-life) with increasing severity of renal dysfunction.…”
Section: Panobinostat Pharmacologymentioning
confidence: 99%
“…Plasma and urine concentrations of panobinostat assessed by liquid chromatography tandem mass spectrometry following administration did not suggest higher drug exposures (C max , AUC, half-life) with increasing severity of renal dysfunction. 18 A formal algorithm for dosing in patients with significant renal dysfunction has not yet been developed.…”
Section: Panobinostat Pharmacologymentioning
confidence: 99%